2018
DOI: 10.3390/resources7040073
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pump Scheduling for Urban Drainage under Variable Flow Conditions

Abstract: The paper is focused on the optimal scheduling of a drainage pumping station, complying with variations in the pump rotational speed and a recurrent pattern for the inflow discharge. The paper is structured in several consecutive steps. In the first step, the experimental set-up is described and results of calibration tests on different pumping machines are presented to obtain equations linking significant variables (discharge, head, power, efficiency). Then, those equations are utilized to build a mixed-integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
(58 reference statements)
0
21
0
2
Order By: Relevance
“…Furthermore, in order to evaluate the water tank cost, C tank 2,W , the computation of the preliminary tank volume is required. The volume has been calculated by Equation (A3) [15]:…”
Section: Appendix Amentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in order to evaluate the water tank cost, C tank 2,W , the computation of the preliminary tank volume is required. The volume has been calculated by Equation (A3) [15]:…”
Section: Appendix Amentioning
confidence: 99%
“…Sustainable growth [8] in this sector could be achieved through several strategies, which aim at an optimal management of water distribution networks. For example, optimal pump scheduling, in both clean water [10][11][12] and drainage [13][14][15][16] pumping systems has been shown to improve energy efficiency. In particular, a recent study [15] showed that an optimal pump scheduling in a drainage system can ensure an average value of recovered energy up to 32%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water demand forecasting is of paramount importance for water supply planning and operation, to ensure continuous service at suitable levels of quantity and pressure. Accurate water demand models are thereby key for approaching intelligent asset management of such physical assets as pumps, valves and water-meters [1][2][3]. Also, thanks to deeper understanding of water demand, it is possible to better propose near real-time operation of urban water supply.…”
Section: Introductionmentioning
confidence: 99%
“…. ,ĉ w are the words into which both time series, Q and C, are respectively encoded using Equation (1). The function dist() can be implemented using a table look-up containing pre-computed distances between letters of the SAX alphabet in use Σ = {α 1 , .…”
Section: Introduction To Saxmentioning
confidence: 99%